The effect of topical voriconazole on conjunctiva in rats as revealed by histopathology and immunohistochemistry. (4th July 2019) - Degirmenci, Cumali; Palamar, Melis; Aktug, Hüseyin; Yigittürk, Gürkan; Veral, Ali; Yagcı, Ayşe
Abstract : The aim of this study was to evaluate the effects of topical voriconazole with histopathological and immunohistochemical analysis of the conjunctiva in rats. Twenty-eight Sprague Dawley rats were divided into four groups as two study (S1, S2) and two control (C1, C2). Voriconazole was instilled four times daily to S1, S2 rats. Physiologic saline (0.9%) was instilled four times daily in C1 and C2 rats. S1 and C1 were followed in a dark room; S2 and C2 were held in a room with sunlight. Impression cytology was performed at 0, 15, 30, 45 and 60th d after instillations. After 2 months of treatment conjunctival tissue was removed for histological and immunohistochemical analysis. In impression cytology evaluation, there was no difference between S1 and S2. At 60 d the difference between S1 and C1 was significant. In other comparisons, there was no difference between S1 and C1, C2. The scores of S2 was higher than C1 and C2 for all comparisons except 15th day scores of S2 and C2. In study groups, epithelial and gland degeneration were higher in S2, but inflammation scores were similar. The comparison of immunreactivity of ERK, TGFβ and E-cadherin were different in the study groups than the control groups for all comparisons. In conclusion, voriconazole has side effects due to phototoxicity including squamous cell carcinoma. Clinicians should particularly be careful with the long-term use of topical voriconazole and should follow-up patients strictly in terms of ocular surface alterations.